Risk Factors for Maternal Mortality in Indonesia: Systematic Review - Dewi Nopiska Lilis; Nesi Novita; Ekadewi Retnosari (OPI Napoli, 2023)
Background: Seventeen Sustainment Development Goals are a joint agreement from countries around the world. Maternal mortality is included in Sustainment Development Goals3, whereby in 2030, the number is expected to decrease significantly. A systematic study has yet to be conducted in Indonesia to assess the factors involved in maternal mortality. This review focuses on the question, what are the risk factors, and which ones exert the most significant influence on maternal mortality in Indonesia? Methods: This systematic review was conducted using the Preferred Reporting Items Checklist for Systematic Review and Meta-Analysis Protocol) involving studies published between 2000 and 2021 through Embase, Scopus, Web of Science, Cochrane library, Medline, ScienceDirect, Google scholar, and Wiley Online Library, in English version. Study quality was assessed using the National Institutes of Health controlled intervention study. The risk of study bias was also assessed using The Risk of Bias in Non-randomized Studies - of Exposure tool. Results: There are 334,105 publications were discovered at initial search. Ten articles were finally eligible for further analysis. Risk factors included in the modifiable category including Prior medical history (40% of ten studies; OR range 3.322 - 20.143), pregnancy complications (40% of ten studies; OR range 2.31 - 9.75), delivery complications (30% of ten studies; OR range 5.08 - 8.5), puerperal complications (20% of ten studies; OR 4.19 - 4.382), parity (30% of ten studies; OR 0.25 - 33.949), Birth space (20% of ten studies; OR 0.49 - 5.806), Nutritional status (20% of ten studies; OR 1.37 - 13.256), delayed referral (30% of ten studies; OR 4.01 - 7.135), living area (30% of ten studies; OR 0.989 - 7.41), number of doctors (10% of ten studies; OR 0.99), triage response time (10% of ten studies; OR 1.88), Obst. resident response time (10% of ten studies; OR 1.02), and ICU waiting time (10% of ten studies; OR 1.01). Meanwhile, the most striking non-modifiable risk factor is the mother's age (40% of ten studies; OR 0.27 - 2.792). Conclusion. The study describes some of the modifiable risk factors that can be used in the country's health policies to improve the quality-of-care activities.